Rotating generator of the current quasirectangular pulses; Modern Technique and Technologies. MTT 2002 - Usachev M. V. (2002, 2002)
The performed investigations allow one to consider the character of the electromechanical transients passing and to form definite recommendations for the usage multidisc generators under conditions of the active load feed by the current quasi-rectangular pulses.